Significant Dark Current Suppression in Organic Photodetectors Using Side Chain Fluorination of Conjugated Polymer (Adv. Funct. Mater. 4/2022). (19th January 2022) - Park, Byoungwook; Jung, Juhyoung; Lim, Dae‐Hee; Lee, Hanbee; Park, Sungjun; Kyeong, Minju; Ko, Seo‐Jin; Eom, Seung Hun; Lee, Seung‐Hoon; Lee, Changjin; Yoon, Sung Cheol
Abstract : Organic Photodetectors Organic photodetectors (OPDs) for sensitive detection of a weak light can be achieved by suppression of dark current density of photo active layers. In article number 2108026, Seung‐Hoon Lee, Changjin Lee, Sung Cheol Yoon, and co‐workers suggest a simple but effective method to reduce the dark current density of OPDs by introducing F atoms to the alkyl side chain of the conjugated polymer, and demonstrate high external quantum efficiency and high detectivity of OPDs.